Penggunaan Bakteri Bacillus spp untuk Pengendalian Jentik Nyamuk Anopheles spp - Yusuf, Yenni (Fakultas MIPA UNM, 2009)
Based on the high incidence and fatality of malaria, a comprehensive management to control the disease, including Anopheles larval control to remove the transmission path, is urgently required. Chemical insecticides used for this purpose is claimed to be less environmentally safe and potentially increase the mosquito resistance.Â Thus, there is a need to use alternative insecticide. Some studies found that Bacillus sphaericus dan Bacillus thuringiensis israeli could effectively kill Anopheles larvae and has a low potency to increase resistency. Besides that, it is environmentally safe and does not affect non-target organisms. Therefore, the use of Bacillus spp as larvicides could be undertaken in malaria control programme especially in endemic areas.